The Spectrum of Inherited Neurological Disorders: Experience from Paediatric Neurology Department of A Tertiary Care Hospital - Shah, Syed Zubair; Sultan, Tipu; Idrees, Sara; Shah, Syed Hussain; Rafique, Shumaila; Alvi, Javeria Raza (Pakistan Armed Forces Medical Journal, 2026)
Objective: To assess the spectrum of inherited neurological disorders presenting in a tertiary care hospital of Pakistan using Whole Exome Sequence (WES) analysis. Study Design: Observational cross-sectional study. Place and Duration of the Study: Department of Pediatric Neurology, University of Child Health Sciences and the Children’s Hospital, Lahore, Pakistan, from July 2021 to March 2023. Methodology: This study included 423 pediatric patients, from both genders, between the ages of 1 month to 18 years, with clinical suspicion of inherited neurological disorders. Samples were taken from the patients for WES examination to reach a genetic diagnosis. Results: Among the 423 patients, 251 (59.34%) were males and 172(40.66%) were female. Ages were distributed in the following categories: 271 (64.10%) were found to be 0-5 years old, 85 (22.50%) were 6-10 years old, 45(10.60%) were 11-15 years old and 12 (2.80%) were 16-20 years old. Consanguinity was noted among parents of 376(88.89%) patients. Occurrence of developmental disorders was noted in 229 (110 WES positive/119 WES negative, DY 48.00%) patients, 66 (31 WES negative/35 WES positive, DY 53.00%) patients had neurometabolic disorders, 54 (21 WES negative/33 WES positive, DY 61.10%) patients had hereditary movement disorders, 45 (15 WES negative/30 WES positive, DY 66.70%) patients had epilepsy while 29 (15 WES negative/14 WES ... Conclusion: The most common group of inherited neurological disorders was degenerative brain disorders with WES having high diagnostic yield as it not only ends diagnostic difficulty, helps better